Kurikulum Adab Untuk SMP Tahfidz Qur’an Pada Masyarakat Minoritas Muslim - Jainudin Oumo; Wido Supraha; Abdul Hayyie Al Kattani (Cakrawala Repositori IMWI, 2023)
Departing from the problems found regarding the manners and morals of memorizing the Qur'an in NTT, some even become apostates in marriage. Therefore the author wants to study and develop methods and inculcation of manners and morals in memorizing the Al-Qur'an, aiming to overcome or prevent similar incidents from happening again in the future. In this thesis the author examines Imam an-Nawawi's concept of the manners of memorizing the Qur'an.This study was formulated to describe the adab curriculum method from the perspective of Imam an-Nawawi in the book “At-Tibyan fii adabi hamatil Qur'aan”, this research is a type of qualitative research and field research with a character study and case study approach, aiming to explore the character's thoughts through Primary and secondary literature related to the object of research is then integrated with field research in an effort to produce the tahfidz Qur'an method based on the adab curriculum in studying and memorizing the Qur'an for the junior high school level.This research resulted in a discussion of the adab curriculum concept in the tahfidz of the Qur'an according to Imam an-Nawawi in the book “At-Tibyan fii adabi hamalatil Qur'an at the junior high school level based on the Al-Qur'ān and Al-Hadith, Ijtihad Ulama internalized through the vision and mission of the school. As for the purpose of using the adab curriculum concept in learning the Qur'an is to create a generation of memorizers of the Qur'an who have noble manners and morals as well as extensive religious knowledge, and strong aqidah according to the understanding of the Companions of the Prophet Muhammad ﷺ . The concept of adab in learning tahfidz Al-Qur'an is exemplary, fun learning, teaching gradually, targhib and tarhib, giving gifts and punishments, holding the other person's hand or shoulder during learning, stories, discussions and questions and answers, showing something that is forbidden to emphasized his unclean, noble methods of personality.The author recommends to all educational institutions as well as Muslims in general to make this research an alternative solution to the problems that occur, especially in current Islamic educational institutions, and Muslim communities in general in Muslim minority areas, in addressing the notion of pluralism, which is carried out by church activists and missionaries.